2009
DOI: 10.1080/03009740802541470
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia and lipoprotein pattern in systemic lupus erythematosus (SLE) and SLE‐related cardiovascular disease

Abstract: sdLDL was not increased and SLE cases and SLE controls had decreased levels of sHDL. VLDL differentiates between SLE cases and SLE controls. The lipid pattern in SLE-related CVD was thus not similar to the pattern seen in diabetes or in CVD in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…This finding is consistent with a possible reduction/dysfunction of the small HDL populations specific for these transporters9 and with a shift to larger HDL, typical acceptors for SR-BI-presented cholesterol, supported also by the much stronger correlation between SR-BI-mediated CEC and total serum HDL levels that we found in SLE compared to controls and RA patients. Indeed, HDL structural alterations described in SLE include size increase 39 40. So, while a similar deficit in the cumulative contribute of ABCG1 and SR-BI-mediated CEC was found in RA and SLE with respect to controls, the profoundly altered ratio between these two pathway-mediated CEC in SLE further supports a complex derangement in the HDL functional pattern specific for this disease, even in presence of normal serum HDL levels.…”
Section: Discussionmentioning
confidence: 79%
“…This finding is consistent with a possible reduction/dysfunction of the small HDL populations specific for these transporters9 and with a shift to larger HDL, typical acceptors for SR-BI-presented cholesterol, supported also by the much stronger correlation between SR-BI-mediated CEC and total serum HDL levels that we found in SLE compared to controls and RA patients. Indeed, HDL structural alterations described in SLE include size increase 39 40. So, while a similar deficit in the cumulative contribute of ABCG1 and SR-BI-mediated CEC was found in RA and SLE with respect to controls, the profoundly altered ratio between these two pathway-mediated CEC in SLE further supports a complex derangement in the HDL functional pattern specific for this disease, even in presence of normal serum HDL levels.…”
Section: Discussionmentioning
confidence: 79%
“…This pattern is consistent with a possible reduction/dysfunction of the small HDL populations (Favari et al 2009) and a shift to larger HDL, typical acceptors of cholesterol effluxed by SR-BI. Indeed, HDLs of SLE patients were found increased in size (Hua et al 2009;Juárez-Rojas et al 2008). The impaired ABCA1-and ABCG1-mediated CEC in SLE patients may have a great impact because cholesterol efflux not only opposes lipid deposition in vessels but is also crucial for the modulation of macrophage, endothelial, and T-cell inflammatory functions (Prosser et al 2012;Yvan-Charvet et al 2010a, b).…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…A retrospective analysis carried out by Bessant et al demonstrated that patients with SLE just prior to a CVD event (MI, angina, cerebrovascular accident [CVA] or peripheral vascular disease) were more likely to have the presence of lupus anticoagulant compared with patients with SLE without CVD, after controlling for disease duration [62]. The presence of antiphospholipid antibodies was an independent predictor of vascular events in multiple prior studies on SLE patients [70,71]. A specific antiphospholipid antibody, anti-β-2-glycoprotein I antibody, has also been associated with increased risk of acute coronary syndrome in the general population [72].…”
Section: Lupus-specific Variablesmentioning
confidence: 99%
“…Hua et al revealed further abnormalities in patients with SLE when they showed that higher VLDL concentrations differentiated SLE patients with CVD from SLE patients who did not have CVD and from general population controls. Interestingly, LDL did not differ significantly between study groups and neither did small, dense LDL [70]. As discussed above, the role of corticosteroids in this lipid profile is not clear.…”
Section: Lupus-specific Variablesmentioning
confidence: 99%